Community Assistance for Eco-Edutourism-Based Tourism Village Development in Rancamaya Village - Achmad Fauzi; Andi Dwi Pangestu; Fauzan Natsir (Outline Publisher, 2026)
Rancamaya Village in South Bogor has significant potential as a tourism village, particularly in agro-tourism based on its renowned durian cultivation, natural scenery, and Sundanese cultural heritage. However, the community faces challenges in developing this potential in an integrated, sustainable manner. This community service activity aimed to assist the community of Rancamaya Village in developing an eco-edutourism-based tourism village through training, facilitation, and mentoring. The methods employed included participatory rural appraisal (PRA), Focus Group Discussion (FGD), workshops, field practice, and ongoing mentoring. The activity involved community members, Pokdarwis management, and local government representatives. The results showed an increase in participants' understanding of eco-edutourism concepts (78%), improvement in the ability to design educational tourism packages, strengthened Pokdarwis institutional capacity, and the formulation of a village tourism development roadmap integrating ecological, educational, and cultural elements. This activity demonstrated that a participatory mentoring approach can effectively accelerate the development of sustainable eco-edutourism in rural communities.